Analisis Pengaruh Variasi Tekanan Dan Dimensi Briket Sekam Padi Terhadap Temperatur Dan Lama Nyala Api - Melvani E. D. Tana; Defmit B.N. Riwu; Adi Y. Tobe (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2021)
This research was conducted to determine the effect of variations in pressure and dimensions of rice husk briquettes on the temperature and duration of the flame. The mashed husk charcoal is mixed with 50 ml of water, 160 grams of starch and 450 grams of rice husk charcoal, stirred until evenly distributed. The process of molding charcoal briquettes that have been mixed and then printed, uses molds with diameters of 1 in, 1.5 in and 2 in, with different briquette pressure variations, pressure variations using sizes 0.1 MPa, 0.2 MPa, 0, 3 MPa, 0.4 MPa. The briquettes are then dried in the sun for three days to dry. From the research, it was found that the variation of pressing pressure affects the characteristics of the flame and the dimensions of the burning of rice husk briquettes. The highest temperature was recorded at 749 0C at 1.5 In briquette size and the pressing pressure was 0.2 MPa. At this size, the longest flame is 18 minutes